Iteration procedure of the stress-strain state analysis for a baR made of falling branch material under pure bending - Struzhanov, Valeriy Vladimirovich (Computational Continuum Mechanics, 2008)
The pure bending of a bar made of falling branch material is considered under the monotonic increasing bending moment (rigid loading) or the monotonic increasing curvature of the bar (soft loading). The iteration procedures of the stress-strain analysis taking into account the capability of the material to work at the stage of softening (falling branch) are presented. A relationship between the stability of the deformation process and the convergence of the iteration procedure has been established.